1995
DOI: 10.1164/ajrccm.151.5.7537586
|View full text |Cite
|
Sign up to set email alerts
|

sVCAM-1 levels after segmental antigen challenge correlate with eosinophil influx, IL-4 and IL-5 production, and the late phase response.

Abstract: Evidence from in vitro studies suggests a potential role for vascular cell adhesion molecule-1 (VCAM-1) in eosinophil trafficking. We hypothesized that induction of VCAM-1 occurs in the lung during IgE-mediated airway inflammation in humans. The technique of segmental antigen provocation followed by bronchoalveolar lavage (BAL) at 24 h was used to study 27 ragweed-allergic asthmatics (AA) and 18 atopic nonasthmatics (ANA). Total and differential cell counts were performed, and IL-4, IL-5, and soluble (VCAM) (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 25 publications
4
46
0
Order By: Relevance
“…We also found that BAL fluid IL-5 correlated with the percentage of eosinophils in BAL and with the magnitude of the late-phase fall in FEV 1 . A correlation between BAL fluid IL-5 and eosinophil recruitment to the airway after segmental Ag challenge has been reported previously (38,(73)(74)(75)(76) and is consistent with the observation that anti-IL-5 therapy causes a significant decrease in sputum eosinophils (1).…”
Section: Discussionsupporting
confidence: 91%
“…We also found that BAL fluid IL-5 correlated with the percentage of eosinophils in BAL and with the magnitude of the late-phase fall in FEV 1 . A correlation between BAL fluid IL-5 and eosinophil recruitment to the airway after segmental Ag challenge has been reported previously (38,(73)(74)(75)(76) and is consistent with the observation that anti-IL-5 therapy causes a significant decrease in sputum eosinophils (1).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, mononuclear cells isolated from serum or BAL fluid samples from atopic asthmatic patients have been found to display an enhanced TH2-type cytokine response when activated by ligand. Moreover, emerging data derived from genetic analyses of family members with allergic asthma have demonstrated a significant direct correlation between altered airway responsiveness and IL-4 and IL-5 cytokine levels in serum or BAL fluid samples (5,19,28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mononuclear cells isolated from serum or BAL fluid samples from atopic asthmatic patients have been found to display an enhanced TH2-type cytokine response when activated by ligand. Moreover, emerging data derived from genetic analyses of family members with allergic asthma have demonstrated a significant direct correlation between altered airway responsiveness and IL-4 and IL-5 cytokine levels in serum or BAL fluid samples (5,19,28).The roles of the TH2 cytokines in allergic asthma have been reasonably well characterized. IL-4 was found to direct immunoglobulin isotype switching to IgE synthesis, and IL-5 was found to be primarily responsible for mast cell and eosinophil differentiation, recruitment, and activation (10-12).…”
mentioning
confidence: 99%
“…The BAL sampling method potentially distorts the microvascular circulation of the lung and the barrier between the blood and air, both through physical trauma and the creation of diffusion gradients, and this is likely to vary substantially between individuals for purely technical reasons that cannot easily be quantified. This may be particularly important in the case of small molecular weight solutes, but it is clear that such considerations should be borne in mind by all groups interpreting the measurements of BAL solute levels, especially in the light of emergent interest in this area, with assays of cytokines [22], soluble adhesion molecules [23], and soluble markers of cellular activation in BAL fluid becoming technically routine [21,24].…”
Section: Discussionmentioning
confidence: 99%